Analisis Implementasi SEO (Search Engine Optimization) dalam Kebutuhan Promosi Online pada Website Masteriwak.id - Haris, Achmad; Dasuki, Mohammad; Arifianto, Deni (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
Digital marketing is the main key in reaching a wider market in the digital era, especially through the use of websites. This research focuses on the implementation of Search Engine Optimization (SEO) to increase the visibility of the Masteriwak.id website, a platform engaged in online koi fish sales. This research uses a quantitative approach with the main stages being an initial performance audit, on-page and off-page SEO optimization, and evaluation of results using Google Search Console and SERPRobot. On-page SEO optimization involves improving internal elements such as meta title, meta description, and website speed, while off-page SEO focuses on strengthening backlinks from quality external sources. The implementation results show a significant increase in impressions, clicks, and keyword rankings on SERPs. For example, the keyword “where to sell koi fish nearby” rose from no rank to position 13 with 35 impressions and 4 clicks. Statistical evaluation using paired-samples t-test shows the difference before and after SEO optimization. The t-test values for the impression parameters were -1.641 (p = 0.243), clicks -2.524 (p = 0.128), and SERP rank -2.535 (p = 0.127), which showed improvement but not yet statistically significant. This study confirms the importance of systematically implementing SEO, although continuous optimization is still required for maximum results.